Detection by monoclonal antibody of carbohydrate antigen CA 50 in serum of patients with carcinoma. Issue 6429 (19th May 1984) - Holmgren, J; Lindholm, L; Persson, B; Lagergård, T; Nilsson, O; Svennerholm, L; Rudenstam, C M; Unsgaard, B; Yngvason, F; Pettersson, S
Abstract : A solid phase radioimmunoassay was devised for measuring the value of the carcinoma associated carbohydrate antigen CA 50 in serum based on the use of a specific monoclonal antibody (C 50). Samples of serum from 259 patients with carcinoma, 114 patients with other malignancies or inflammatory diseases, and 150 healthy controls were examined. Serum values of CA 50 exceeding the mean plus three standard deviations for control samples from blood donors were found in a high proportion of patients with colorectal adenocarcinomas (50% of those with early, localised tumours and 75% of advanced cases), other gastrointestinal carcinomas (69%), uterine cancer (75% of those with corporeal and 88% of those with cervical cancer), prostatic cancer (90%), lung cancer (52%), and breast, ovarian, kidney, and urinary bladder carcinoma (26-67%). The CA 50 values in samples from patients with inflammatory diseases, including ulcerative colitis, with rare exceptions (0-7%) were within the normal range, as were those in patients with various sarcomas and malignant melanoma. Measuring serum values of CA 50, which is evidently a generalised carcinoma associated antigen, may be useful in clinical research studies of the diagnosis, management, and prognosis of patients with different types of carcinoma.